2023
DOI: 10.1029/2022jd037934
|View full text |Cite
|
Sign up to set email alerts
|

Observation‐Driven Characterization of Soil Moisture‐Precipitation Interactions in the Central United States

Abstract: Soil moisture feedbacks that initiate, enhance, or suppress convection initiation and precipitation are important components of regional hydroclimatology. However, soil moisture feedbacks and the processes through which they operate are notoriously challenging to observe and study outside of model environments. In this study, we combine a climatological assessment of event frequency‐based measurements of soil moisture‐precipitation coupling in the central United States with a process‐based analysis of the mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Considering local impacts, Dirmeyer et al [29] observed a significant correlation between precipitation errors and errors in latent heat flux. The surface heat flux plays a pivotal role in SM-P [30]. Research conducted by Lawston-Parker et al [31] revealed that in relatively moist soil conditions, the proportion of latent heat flux (LH) intensifies, consequently lowering the lifting condensation level (LCL) height and creating a favorable environment for precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…Considering local impacts, Dirmeyer et al [29] observed a significant correlation between precipitation errors and errors in latent heat flux. The surface heat flux plays a pivotal role in SM-P [30]. Research conducted by Lawston-Parker et al [31] revealed that in relatively moist soil conditions, the proportion of latent heat flux (LH) intensifies, consequently lowering the lifting condensation level (LCL) height and creating a favorable environment for precipitation.…”
Section: Introductionmentioning
confidence: 99%